PENGARUH STRUKTUR MODAL, SALES GROWTH, FIRM SIZE, DAN TOTAL ASSETS TURNOVER TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Ika Prasetyowati, 10.05.51.0093; Irsad, Moch. (Students Journal of Economic and Management, 2014)
This present study examines the effect of capital structure, sales growth, firm size, and total assets turnover on profitability in manufacturing companies. The population in this study is manufacturing companis that is listed on the Indonesia Stock Exchange during the years 2009- 2010. The sample of this study is taken using purposive sampling and obtain a sample of 105 sample companies Companyâs data was examined by the normality examination, multicolinearity, autocorrelation, heteroscedasticity. The results showed normality data and free from the classic assumption examination. Furthermore, regression analysis was used to describe the relationship between these variables. Based on the research that has been conducted shows that capital structure variable has negative and significant effect on the profitability. Sales growth has negative and no significant effect on the profitability. Firm size and total assets turnover have positive and significant effect on the profitability.Keywords: capital structure, sales growth, firm size, total assets turn over, and profitability